DETERMINANTS OF PURCHASE INTENTION FOR ELECTRIC MOTORCYCLES IN DENPASAR CITY - David Sinarta; Anak Agung Ketut Ayuningsasi (Adisam Publisher, 2025)
Global warming poses a significant challenge to sustainable development. Various countries are exploring deeper strategies to achieve a low-carbon and sustainable economy. Indonesia is among the largest contributors to carbon emissions, particularly from the transportation sector. Electric vehicles have substantial potential to reduce carbon emissions and support a cleaner energy transition. The implementation of electric vehicles is expected to reduce dependence on fossil fuels and improve energy efficiency. Therefore, this study aims to analyze the influence of perceived usefulness, perceived ease of use, motor vehicle tax (PKB) incentives, and income on the purchase intention of electric motorcycles in Denpasar City. The sampling method employed was purposive sampling, a type of non-probability sampling, with a total of 100 respondents. Data collected through questionnaires were analyzed using multiple linear regression analysis. The findings indicate that perceived usefulness, perceived ease of use, motor vehicle tax (PKB) incentives, and income simultaneously have a significant effect on the purchase intention of electric motorcycles in Denpasar City. Partially, the results also show that each of these variables perceived usefulness, perceived ease of use, motor vehicle tax (PKB) incentives, and income has a positive and significant effect on purchase intention.